Savagery in right-wing populist leadership: between theatricality and political social engineering - Pierzchalski , Filip (Society Register, 2022)
Contemporary leadership practices in politics are full of emotions, which, on the one hand, may be a manifestation of various types of expressions or moods in the individual and collective dimension, and on the other hand, are an important source of political mobilization or an instrument enhancing effectiveness in the election competition. In this article inducing and politicizing savagery among followers – defined as an emotional social engineering strategy for articulating given goals and interests – will be treated as a populist manifestation and an expression of planned radicalization of political competition. The aim of the article is a meta theoretical reflection on the instrumentalisation of wildness in the leadership of the right-wing populist – Donald Trump. A practical rationale for discussing collective savagery in politics will be the attack on the Capitol in Washington on January 6, 2021. This event will serve as an example to explain the political exteriorization of the confrontational Trump followers, thanks to which the right-wing populist leader not only articulated his own goals, shaped public self-presentation or theatrical political presence, but also redefined and challenged the existing rules and principles of democratic political culture.